Identification of the Oncogenic Role of MSH2 in the Stemness and Progression of Glioma Through Regulating Wnt Signaling Pathway - Jun Liu; Jiayu Chen; Lianglei Jiang (Cancer Medicine, 2025)
ABSTRACT Background Glioma is one of the most aggressive brain tumors, and its progression is often associated with stemness maintenance and therapy resistance. The role of MSH2 in glioma remains largely unclear. Methods We analyzed public datasets and clinical samples to assess MSH2 expression and its clinical relevance. Functional assays in vitro and in vivo were performed to investigate the effects of MSH2 knockdown on glioma cell behavior. Mechanistic studies were conducted to explore downstream signaling pathways and stemness regulation. Results MSH2 was found to be significantly upregulated in glioma tissues and cell lines, and its high expression correlated with poor prognosis. Silencing MSH2 inhibited cell proliferation, migration, and tumor growth, while promoting apoptosis and G2 cell cycle arrest. Mechanistically, phospho‐kinase screening and rescue experiments suggested that MSH2 promotes glioma progression via activation of the Wnt/β‐catenin signaling pathway. Furthermore, MSH2 knockdown suppressed the expression of stemness markers, impaired sphere formation, and sensitized glioma cells to cisplatin treatment. Conclusions Our study identifies MSH2 as an oncogenic factor in glioma, which drives stemness and progression through regulation of the Wnt/β‐catenin pathway, and may serve as a potential therapeutic target.